Pengembangan Masyarakat melalui Lembaga Hisbah dalam Meningkatkan Ekonomi Umat - Nur Azdifah (Fakultas Dakwah IAIN Jember, 2019)
In today's human life where the times are increasingly advanced, there are many new thoughts and understandings, also advanced from all scientific fields as well as practicality. Therefore, it is necessary to have an institution that guides and maintains the nation's morals. An example of this institution is the Indonesian Ulema Council (MUI). In this case we can know how important and necessary to revive the Hisbah institution for the Islamic economy today and from this we also want to discuss more deeply how the Hisbah institution can improve business through Sharia principles. In this paper, the method used by the author is descriptive qualitative research. Hisbah comes from Arabic, rooted in the word which has quite a variety of meanings, such as calculating, estimating, calculating, thinking, opinions, views and others. business activities in various forms that are not limited by the amount (quantity) of ownership of their assets (goods and services) including profits, but are limited in the way of obtaining and utilizing their assets (there are halal and haram rules). Islamic principles in business, among others. a) The principle of monotheism b) The principle of piety and pleasure c) Equilibrium (balance of justice) d) Benefit